2015
DOI: 10.1158/1078-0432.ccr-14-3322
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Transcriptional Profiling to Improve Personalized Diagnosis and Management of Cutaneous T-cell Lymphoma (CTCL)

Abstract: Purpose While many Mycosis Fungoides (MF) patients presenting with stage I disease enjoy an indolent disease course and normal life expectancy, about 15-20% of them progress to higher stages, and most ultimately succumb to their disease. Currently, it's not possible to predict which patients will progress and which patients will have a stable disease. Previously, we conducted microarray analyses with RT-PCR validation of gene expression in biopsy specimens from 60 stage I-IV CTCL patients, identified three dis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
83
4
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(99 citation statements)
references
References 57 publications
8
83
4
3
Order By: Relevance
“…Enhanced STAT5 signaling was also linked to overexpression of oncogenic miR-155 in CTCL [86], associated with downregulation of tumor-suppressive miR-22 [87], or enhanced disease progression caused by Lymphotoxin-α-dependent lymphangiogenesis [88]. STAT5-dependent CD80 expression was also linked to resistance to Vorinostat and risk of disease progression in PTCL [84,89,90]. …”
Section: Targets In Ptcl and Driver Mutationsmentioning
confidence: 99%
“…Enhanced STAT5 signaling was also linked to overexpression of oncogenic miR-155 in CTCL [86], associated with downregulation of tumor-suppressive miR-22 [87], or enhanced disease progression caused by Lymphotoxin-α-dependent lymphangiogenesis [88]. STAT5-dependent CD80 expression was also linked to resistance to Vorinostat and risk of disease progression in PTCL [84,89,90]. …”
Section: Targets In Ptcl and Driver Mutationsmentioning
confidence: 99%
“…Notably, we identified several genes that were previously reported to correlate with CTCL biological activities (CCL7, CCL17, CCL18, CCL22, CCL26 and CXCL12) [8,9,[13][14][15]. Moreover, among the upregulated MMP-related genes, the mRNA expression of MMP12, which was previously correlated with the risk of progression of MF [8], was highly upregulated (Fig. 1). 3.2.…”
Section: The Immunomodulatory Effects Of Il-4 On Cd163+ Macrophagesmentioning
confidence: 63%
“…These in vitro data suggested that IL-4 polarizes macrophages into type 2 (M2) macrophages. To further analyze the M2 differentiation in macrophages by the stimulation of IL-4, we performed DNA microarray analysis, which suggested that monocyte-derived macrophages could obtain the ability by IL-4 stimulation to produce chemokines that had been correlated with CTCL biological activities [8,9,[13][14][15]. These reports suggest that chemokines derived from TAMs stimulated by IL-4 play a crucial role in the progression of advanced MF.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations